Complete Recovery From Severe Tachycardia-Induced Cardiomyopathy in a Patient With Ebstein's Anomaly. (July 2014) - Stämpfli, Simon F.; Plass, André; Müller, Andrea; Greutmann, Matthias
We report the case of a young patient with repaired Ebstein's anomaly who developed severe tachycardia-induced cardiomyopathy and a large apical thrombus as a consequence of sustained atrial flutter with a 2:1 conduction. In spite of a dramatic course in hospital with prolonged mechanical resuscitation and extracorporeal membrane oxygenation, she survived and made a rapid and full recovery. This remarkable case underlines that atrial arrhythmias, the most common complication in adults with congenital heart disease, may have devastating outcomes when timely recognition is missed and treatment delayed—thus, emphasizing the importance of good patient education.